Challenges and Lessons from the COVID-19 Pandemic for Health Surveillance in Brazil: Reflections on Technologies, Models, and System Organization - Henriques, Claudio Maierovitch Pessanha (2024)
The term "health surveillance" encompasses a wide range of activities, including the monitoring and observation of illnesses and diseases. In this section, we will examine the most well-known aspect of health surveillance, namely the monitoring of communicable diseases. To illustrate our discussion, we will use the ongoing pandemic caused by the SARS-CoV-2 virus as a case study. As the text progresses, the focus shifts to an examination of technologies, models, and the structure of the system. The most severe epidemic of our era, classified as a pandemic due to its global impact, has compelled us to reflect on a multitude of disciplines. The resulting suffering should preclude any association with positive images, despite the opportunity to learn and, in some instances, observe the capacity of humans to act in solidarity. It is often observed that few things are as didactic as tragedies and mistakes. It is therefore important to explore them carefully to extract the necessary feedback to correct the course of action in health. In this text, we will discuss the conditions that led health surveillance in Brazil to fail miserably in its mission in the face of the emergency triggered by the novel coronavirus disease 2019. We will also present points that deserve attention in a restructuring of the health surveillance system.